2018
DOI: 10.1021/acs.langmuir.8b01900
|View full text |Cite
|
Sign up to set email alerts
|

CH4 Nanobubbles on the Hydrophobic Solid–Water Interface Serving as the Nucleation Sites of Methane Hydrate

Abstract: The surface hydrophobicity of solid particles plays a critical role in the nucleation of gas hydrate formation, and it was found that the hydrophobic surface will promote this nucleation process, but the underlying mechanism is still unveiled. Herein, we proposed for the first time our new theory that the formation of methane nanoscale gas bubbles on the hydrophobic surface provides the nuclei sites for further formation of methane hydrate. First, we studied the effect of hydrophobicity of particles on the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…Soon after that, Guo et al reported experimental evidence of methane bubbles on hydrophobic surfaces as nucleation sites for hydrate formation. 136 In their study, methane hydrate formation was found to be promoted on hydrophobic graphite surfaces, but not so on hydrophilic mica surfaces. As characterized by atomic force microscopy (AFM), a large number of methane nanobubbles with an average diameter ∼223.4 nm were observed on the graphite surfaces, which were not observed on the mica surfaces.…”
Section: Anti-hydrate Deposition Surfacesmentioning
confidence: 92%
See 3 more Smart Citations
“…Soon after that, Guo et al reported experimental evidence of methane bubbles on hydrophobic surfaces as nucleation sites for hydrate formation. 136 In their study, methane hydrate formation was found to be promoted on hydrophobic graphite surfaces, but not so on hydrophilic mica surfaces. As characterized by atomic force microscopy (AFM), a large number of methane nanobubbles with an average diameter ∼223.4 nm were observed on the graphite surfaces, which were not observed on the mica surfaces.…”
Section: Anti-hydrate Deposition Surfacesmentioning
confidence: 92%
“…Although experiments showed hydrate deposits formed in water-dominated systems and caused large pressure drop, 132,135 it was not until 2018 that Guo et al successfully observed hydrate deposition initiated by gas bubbles on surfaces with the existence of saturated water. 136 As such, mechanisms I and II both posit that hydrate deposition arises from hydrate formers on pipe walls, despite their occurrence in distinct systems. In contrast, mechanism III subscribes to the view that the hydrate deposits onto surfaces through a cohesion process between hydrate particles.…”
Section: Anti-hydrate Deposition Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, multiple experimental studies have demonstrated the outstanding clathrate promoting effects of hydrophobized silica surfaces. [27][28][29][30] Nevertheless, considering the diversity of types, distribution and concentration of surface ligands available to be introduced into SiO 2 matrices, as well as the different pore sizes of the parent matrix, it is important to establish clear structure-property relationships to guide the choice of high-performance materials without having to rely on serendipity-based experiments.…”
Section: Introductionmentioning
confidence: 99%